Protective base film for optical cement and preparation method of protective base film

By adding functional masterbatches such as polyethylene naphthalate to the protective base film for optical glue and mixing them with the first polyester, the problem of additives and auxiliary materials affecting transparency and haze in the prior art is solved, and high light transmittance, low haze and good heat resistance are achieved.

CN119682361AActive Publication Date: 2025-03-25江苏慧智新材料科技有限公司

Patent Information

Application Number
CN202411915165.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-25
Estimated Expiration
2044-12-24

AI Technical Summary

Technical Problem

In the process of improving smoothness and winding effect of existing protective base films for optical adhesives, the addition of additives and auxiliary materials will affect their transparency and haze, resulting in a degradation of optical performance.

Method used

By adding functional masterbatches such as polyethylene naphthalate to the protective base film and mixing them with the first polyester, the dispersion of the base film is optimized, its light transmittance and heat resistance are improved, and haze is reduced.

Benefits of technology

The high light transmittance, low haze and good heat resistance of the protective base film for optical glue are achieved, and its optical performance and stability are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005206663240000081
    Figure BDA0005206663240000081
  • Figure BDA0005206663240000091
    Figure BDA0005206663240000091
Patent Text Reader

Abstract

The invention discloses a protective base film for optical cement, comprising: a core layer sandwiched between a first surface layer and a second surface layer; the core layer comprises first polyester; each of the first surface layer and the second surface layer comprises first polyester and functional master batches in a mass ratio of (45-50): (50-55), and the functional master batches comprise polyethylene naphthalate, second polyester and modified barium sulfate. The dispersity is improved by mixing the functional master batch and the first polyester, so that the haze and the light transmittance of the base film are optimized; through the functional master batch prepared from the polyethylene naphthalate, the heat resistance and the stability of the base film are optimized, the transmittance of the base film is improved, and the haze is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of optical films, and in particular to a protective base film for optical adhesive and a preparation method thereof. Background Art

[0002] Optical transparent adhesive is also called OCA optical adhesive protective base film optical adhesive, which has extremely high light transmittance, good optical properties and high adhesion, and is widely used in capacitive and resistive touch screen technologies. At least one surface of the optical transparent adhesive is provided with a protective film, which is required to meet the high light transmittance to ensure that it does not affect the optical properties of the final product. The commonly used base material of the protective film is biaxially oriented polyester film (BOPET). In order to improve the smoothness of the film, improve the surface friction coefficient, etc., and thus improve the winding effect of the polyester film, and facilitate the subsequent processing of anti-adhesion, a certain amount of additives and auxiliary materials are often required to be added, but their addition will affect the transparency and haze of the polyester film.

[0003] Therefore, it is necessary to improve the protective base film for optical adhesive in the prior art. Summary of the invention

[0004] One of the purposes of the present invention is to overcome the defects existing in the prior art and provide a protective base film for optical adhesive, which improves the dispersibility by mixing a functional masterbatch with a first polyester, thereby optimizing the haze and transmittance of the base film; the functional masterbatch prepared by polyethylene naphthalate is used to optimize the heat resistance and stability of the base film, and improve its transmittance and reduce the haze.

[0005] In order to achieve the above-mentioned process effect, the technical solution of the present invention is: a protective base film for optical adhesive, comprising:

[0006] A core layer, sandwiched between the first surface layer and the second surface layer;

[0007] The core layer includes a first polyester;

[0008] The first surface layer and the second surface layer both include a first polyester and a functional masterbatch in a mass ratio of (45-50):(50-55), and the functional masterbatch includes polyethylene naphthalate, a second polyester and modified barium sulfate.

[0009] The preferred technical solution is: the functional masterbatch comprises 30-40 parts of polyethylene naphthalate, 60-70 parts of the second polyester and 1-2 parts of modified barium sulfate, calculated by weight.

[0010] The preferred technical solution is: the modifier of the modified barium sulfate is silicate and / or aluminum salt.

[0011] The preferred technical solution is: the second polyester is prepared by esterification of a dibasic acid and a diol by a catalyst, the dibasic acid includes terephthalic acid and 1,4-cyclohexanedicarboxylic acid, and the diol includes ethylene glycol and isomannide.

[0012] The preferred technical solution is: the molar ratio of terephthalic acid, 1,4-cyclohexanedicarboxylic acid, isomannide and ethylene glycol is (97-98): (2-3): (2-2.5): (97.5-98).

[0013] The preferred technical solution is: the catalyst is an antimony-based catalyst.

[0014] The preferred technical solution is: the ratio of the thickness of the first surface layer, the core layer and the second surface layer is (4-4.5): (91-92): (4-4.5). The total thickness of the protective base film is 38-100 μm.

[0015] The second object of the present invention is to overcome the defects in the prior art and provide a method for preparing a protective base film for optical adhesive, comprising the following steps:

[0016] S1: Preparation of functional masterbatch;

[0017] S2: The raw materials of the first surface layer, the core layer and the second surface layer are melted separately and cast into sheets;

[0018] S3: The molded casting is preheated for the first time, stretched longitudinally, and cooled for the first time;

[0019] S4: the longitudinally stretched cast sheet is sequentially subjected to a second preheating, heating and transverse stretching, heat setting and a second cooling to obtain the protective base film;

[0020] The raw material melting of the core layer adopts a single screw, and the temperature of the melt extruder is set to 180±2℃, 270±2℃, 280±2℃, 285±2℃, 285±2℃, 285±2℃, 285±2℃, 285±2℃, 285±2℃, 280±2℃ in sequence, and the temperature of the metering extruder is set to 270-280℃;

[0021] The raw material melting of the first surface layer and the second surface layer adopts a twin-screw, and the melting and metering are integrated. The extrusion temperatures are set to 290±2℃, 290±2℃, 285±2℃, 280±2℃, 275±2℃, 270±2℃, and 270±2℃ respectively.

[0022] The preferred technical solution is: during the preparation of the functional masterbatch in S1, the temperature of the raw material mixing and melting is 290-295°C.

[0023] The preferred technical solution is: in S3, the first preheating temperature is 60-90°C, the longitudinal stretching temperature is 70-100°C, the longitudinal stretching ratio is 3-3.6 times, and the longitudinal stretching rate is 80-120 m / min;

[0024] In S4, the second preheating temperature is 60-90° C., the transverse stretching temperature is 180-200° C., the transverse stretching ratio is 3-3.8 times, and the transverse stretching rate is 80-120 m / min;

[0025] The heat setting temperature is 220-240°C.

[0026] The advantages and beneficial effects of the present invention are:

[0027] The protective base film for optical adhesive improves dispersibility by mixing functional masterbatch with the first polyester, thereby optimizing the haze and transmittance of the base film; the functional masterbatch prepared by polyethylene naphthalate optimizes the heat resistance and stability of the base film, improves its transmittance and reduces haze. DETAILED DESCRIPTION

[0028] The specific implementation of the present invention is further described below in conjunction with the examples. The following examples are only used to more clearly illustrate the technical solutions of the present invention, and cannot be used to limit the protection scope of the present invention.

[0029] First Polyester

[0030] It is high gloss polyester chips, and further, it is Sinopec FG600.

[0031] Functional Masterbatch

[0032] Calculated by weight, it comprises 30-40 parts of polyethylene naphthalate, 60-70 parts of the second polyester and 1-2 parts of modified barium sulfate.

[0033] Among them, polyethylene naphthalate (PEN) has better gas barrier properties than polyethylene terephthalate (PET), which improves the gas barrier properties of the base film; the glass transition temperature (Tg) of PEN is about 40°C higher than that of PET, which means that it can maintain shape stability and dimensional stability at higher temperatures, and improve the heat resistance of the base film; due to the presence of rigid naphthalene rings in the molecular structure of PEN, it usually exhibits lower birefringence and higher transparency, which optimizes the transparency of the base film and solves the problem of excessive haze increase caused by the addition of inorganic particles to the base film. It takes into account the economy of PET and the heat resistance and gas barrier properties of PEN. If the amount of PEN added is too much, the compatibility with PET is poor and the cost is increased. If the amount of PEN added is too little, the haze of the base film surface layer is not well optimized.

[0034] In order to optimize the compatibility between the raw materials, as well as the compatibility between the first and second surface layers and the core layer, the second polyester is prepared by esterification of dibasic acids and diols by a catalyst, the dibasic acids include terephthalic acid and 1,4-cyclohexanedicarboxylic acid, and the diols include ethylene glycol and isomannose. Furthermore, the molar ratio of terephthalic acid, 1,4-cyclohexanedicarboxylic acid, isomannose and ethylene glycol is (97-98): (2-3): (2-2.5): (97.5-98). Isomannose is derived from plant ingredients such as starch and cellulose, and the utilization of biomass resources is a key component in building a green circular economic system. The addition of isomannose can improve the transmittance of the base film and reduce the haze, but excessive addition will cause the yellowing of the base film to increase, resulting in a decrease in transmittance. In order to improve the shortcoming of polyester that it is easy to yellow during the synthesis process, 1,4-cyclohexanedicarboxylic acid is used to destroy the regularity of the polyester chain segment structure, increase the steric hindrance of the chain segment thermal motion, reduce the crystallization ability, and reduce the haze of the base film. However, excessive addition will lead to a decrease in the heat resistance of the base film surface. Antimony-based catalysts are highly efficient and stable, and can well control the degree of polymerization. Further, antimony trioxide (Sb2O3) and / or ethylene glycol antimony (EGS). Furthermore, the amount of antimony-based catalyst added is 100ppm to 200ppm relative to the mass of polyester. Titanium-based catalysts are highly active, can effectively promote esterification reactions, and are environmentally friendly, but the resulting polyester product has a relatively large haze.

[0035] Among them, the refractive index of barium sulfate is similar to that of the first polyester, and the evenly dispersed barium sulfate has a positive effect on the haze and transparency of the base film. The particle size of barium sulfate is 100-120nm. In order to improve the dispersibility of barium sulfate, the surface of barium sulfate is modified, and the modifier of the modified barium sulfate is silicate and / or aluminum salt. Water-soluble NaSiO3 is added to the slurry of BaSO4, and the pH is neutralized with acid to 8-9, so that silicon is precipitated on the surface of BaSO4 particles in the form of Si(OH)4, forming a dense epidermal film of amorphous hydrated silicon oxide; soluble NaAlO2 is added to the slurry of BaSO4, and the pH is neutralized with acid to 9-10, so that aluminum is precipitated on the surface of BaSO4 particles in the form of Al(OH)3, forming a dense inorganic film. The particle size of the modified barium sulfate is 200-220nm.

[0036] In the preparation of functional masterbatch, the temperature of the internal mixer for melting and mixing the raw materials is controlled at 290-295° C. to improve the esterification reaction between PEN and PET, thereby improving the compatibility. Furthermore, the mixing time is 18-20 minutes.

[0037] Example 1

[0038] The protective base film for optical adhesive comprises a core layer, a first surface layer and a second surface layer, wherein the core layer is sandwiched between the first surface layer and the second surface layer; wherein the core layer is a high-gloss polyester chip FG600; the first surface layer and the second surface layer both comprise high-gloss polyester chips FG600 and functional masterbatches in a mass ratio of 47.5:52.5, wherein the functional masterbatch comprises 35 parts of polyethylene naphthalate, 65 parts of a second polyester and 1.5 parts of modified barium sulfate in parts by mass.

[0039] The second polyester is prepared by esterification of terephthalic acid, 1,4-cyclohexanedicarboxylic acid, isomannide and ethylene glycol in a molar ratio of 97.5:2.5:2.2:97.8 through a catalyst. The modifier of the modified barium sulfate is silicate.

[0040] The method for preparing the protective base film for optical adhesive comprises the following steps:

[0041] S1: Prepare functional masterbatch, put the raw materials into internal mixer for melting and mixing, control the temperature at 292℃, and mix for 18min;

[0042] S2: The raw materials of the first surface layer, the core layer and the second surface layer are melted respectively and cast into sheets, wherein the raw materials of the core layer are melted by a single screw, and the temperatures of the melt extruder are set to 180°C, 270°C, 282°C, 285°C, 285°C, 285°C, 285°C, 285°C, 285°C, 280°C in sequence, and the metering extruder is provided with nine zones in total, and the temperatures of each zone are 270°C, 270°C, 270°C, 270°C, 270°C, 270°C, 270°C, 270°C, 282°C in sequence; the raw materials of the first surface layer and the second surface layer are melted by a twin screw, and melting and metering are integrated, and the extrusion temperatures are set to 290°C, 290°C, 285°C, 280°C, 275°C, 270°C, 270°C in sequence, so that the first polyester and the functional masterbatch are evenly mixed, the esterification of the raw materials is promoted, and the compatibility of the two is further improved;

[0043] S3: The first preheating temperature of the molded sheet is 80°C, the longitudinal stretching is at 88°C, the stretching ratio is 3.4 times, the stretching rate is 100m / min, and the first cooling is performed;

[0044] S4: The longitudinally stretched cast sheet is sequentially subjected to a second preheating temperature of 80°C, heating and transverse stretching at a temperature of 185°C, a stretching ratio of 3.6 times, a stretching rate of 110 m / min, a heat setting temperature of 230°C and a second cooling to obtain the protective base film.

[0045] The thickness of the first surface layer is 2 μm, the thickness of the core layer is 46 μm, and the thickness of the second surface layer is 2 μm.

[0046] Example 2

[0047] Example 2 is based on Example 1, except that the first surface layer and the second surface layer both include high gloss polyester chips FG600 and functional masterbatch in a mass ratio of 50:50. Other components and processes remain unchanged.

[0048] Example 3

[0049] Example 3 is based on Example 1, except that the first surface layer and the second surface layer both include high gloss polyester chips FG600 and functional masterbatch in a mass ratio of 45:55. Other components and processes remain unchanged.

[0050] Example 4

[0051] Example 4 is based on Example 1, except that the functional masterbatch includes 30 parts of polyethylene naphthalate, 70 parts of the second polyester and 1.5 parts of modified barium sulfate. The other components and processes remain unchanged.

[0052] Example 5

[0053] Example 5 is based on Example 1, except that the second polyester is prepared by esterification of terephthalic acid, 1,4-cyclohexanedicarboxylic acid, isomannide and ethylene glycol in a molar ratio of 95:5:2.2:97.8 through a catalyst. Other components and processes remain unchanged.

[0054] Example 6

[0055] Example 6 is based on Example 1, except that the second polyester is prepared by esterification of terephthalic acid, 1,4-cyclohexanedicarboxylic acid, isomannide and ethylene glycol in a molar ratio of 97.5:2.5:6:94 through a catalyst. Other components and processes remain unchanged.

[0056] Example 7

[0057] Example 7 is based on Example 1, except that the thickness of the first surface layer is 1 μm, the thickness of the core layer is 48 μm, and the thickness of the second surface layer is 1 μm. Other components and processes remain unchanged.

[0058] Example 8

[0059] Example 8 is based on Example 1, except that, in the preparation process of the functional masterbatch in S1, the temperature of the raw material mixing and melting is 280° C. The composition remains unchanged, and the other process steps and conditions remain unchanged.

[0060] Comparative Example 1

[0061] Comparative Example 1 is based on Example 1, except that the functional masterbatch includes 100 parts of the second polyester and 1.5 parts of modified barium sulfate. Other compositions and processes remain unchanged.

[0062] Comparative Example 2

[0063] Comparative Example 2 is based on Example 1, except that the first surface layer and the second surface layer both include a first polyester, polyethylene naphthalate, a second polyester and modified barium sulfate, that is, polyethylene naphthalate, the second polyester and modified barium sulfate are not prepared as masterbatches for use, but are directly added and mixed with the first polyester.

[0064] Comparative Example 3

[0065] Comparative Example 3 is based on Example 1, except that the functional masterbatch includes 35 parts of polyethylene naphthalate, 65 parts of the first polyester and 1.5 parts of modified barium sulfate. The other components and processes remain unchanged.

[0066] Performance test of base film:

[0067] 1. Haze, transmittance and stability test

[0068] Instrument: AT-4725 transmission haze meter from BYK, Germany; Test standard: Tested according to ASTM D1003;

[0069] Five samples were taken from the obtained product polyester film, the sample size was 10*10 cm, and the sample cutting direction was consistent with the transverse and longitudinal directions of the polyester film. The haze value and transmittance of the five samples were measured using a transmission haze meter to obtain the average haze value H1 and the average transmittance value T1.

[0070] 2. Heat resistance test

[0071] Take 5 samples from the polyester film of the obtained product, the sample size is 1000mm×1000mm, lay the samples flat on a flat black marble plate, use a feeler gauge to measure the gap between the corners and sides of the sample and the marble plate, and rate them according to the following method: after heat treatment at 150℃ for 30min, the number of protrusions with protrusion height ≥1mm and protrusion depth L≥100mm, and the number of protrusions with protrusion height ≥0.5mm and protrusion depth L≥10mm;

[0072] △: The number of protrusions with a protrusion height ≥1mm and a protrusion depth L≥100mm is ≤2, and the number of protrusions with a protrusion height ≥0.5mm and a protrusion depth L≥10mm is ≤5;

[0073] ▲: The number of protrusions with a protrusion height ≥1mm and a protrusion depth L≥100mm is ≤2, and the number of protrusions with a protrusion height ≥0.5mm and a protrusion depth L≥10mm is ≤6;

[0074] ■: The number of protrusions with a protrusion height ≥1mm and a protrusion depth L≥100mm is greater than 2 or the number of protrusions with a protrusion height ≥0.5mm and a protrusion depth L≥10mm is greater than 6;

[0075] Among them, △ and ▲ are qualified, and ■ is unqualified.

[0076] 3. Friction coefficient measurement

[0077] Instrument: Jinan Labthink PARAM MXD-02 Friction Coefficient Tester; Test Standard: According to ASTM D1894 test, the dynamic friction coefficient is above 0.35 and the static friction coefficient is above 0.36, indicating good anti-adhesion effect.

[0078] The measurement results of the embodiments and comparative examples are shown in the following table:

[0079]

[0080]

[0081] Compared with Example 1, in Example 2 and Example 3, the reduced amount of functional masterbatch added has a negative effect on the heat resistance of the base film, and the increased amount of functional masterbatch added has a negative effect on the haze of the base film.

[0082] Compared with Example 1, the content of PEN in the functional masterbatch of Example 4 is reduced, which has a negative impact on the haze and heat resistance of the base film.

[0083] In Example 6, compared with Example 1, the proportion of isomannide is increased to reduce haze, but due to the high content, the resulting film is yellowed, resulting in reduced light transmittance and poor appearance.

[0084] In Example 7 compared to Example 1, the thickness of the first surface layer and the second surface layer is too thin, and the scattering point density between the barium sulfate particles and the substrate interface is relatively increased, resulting in more light scattering, thereby increasing the haze, poor heat resistance, increased roughness, and poor appearance.

[0085] In Example 8, compared with Example 1, the temperature of melt mixing of the masterbatch is too low, resulting in poor esterification reaction between polyethylene naphthalate and the second polyester, and the compatibility between the two is deteriorated, which has a negative impact on haze, transmittance and heat resistance.

[0086] Compared with Example 1, Comparative Examples 1 and 3 show that polyethylene naphthalate and the second polyester are both essential for improving the optical properties of the base film.

[0087] In Comparative Example 2, compared with Example 1, polyethylene naphthalate, the second polyester and modified barium sulfate are directly mixed with the first polyester. Since the time for melt mixing of polyethylene naphthalate, the first polyester and the second polyester is short, the esterification reaction is insufficient, resulting in poor compatibility, and poor dispersibility of the modified barium sulfate, resulting in severe local adhesion, which has a negative impact on the haze, transmittance and heat resistance of the base film.

[0088] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A protective base film for optical adhesive, comprising: A core layer, sandwiched between the first surface layer and the second surface layer; Characterized in that the core layer comprises a first polyester; The first surface layer and the second surface layer both include a first polyester and a functional masterbatch in a mass ratio of (45-50):(50-55), and the functional masterbatch includes polyethylene naphthalate, a second polyester and modified barium sulfate.

2. The protective base film for optical adhesive according to claim 1, characterized in that: Calculated by weight, the functional masterbatch includes 30-40 parts of polyethylene naphthalate, 60-70 parts of the second polyester and 1-2 parts of modified barium sulfate.

3. The protective base film for optical adhesive according to claim 1 or 2, characterized in that: The modifier of the modified barium sulfate is silicate and / or aluminum salt.

4. The protective base film for optical adhesive according to claim 1 or 2, characterized in that: The second polyester is prepared by esterification of a dibasic acid and a diol by a catalyst, wherein the dibasic acid comprises terephthalic acid and 1,4-cyclohexanedicarboxylic acid, and the diol comprises ethylene glycol and isomannide.

5. The protective base film for optical adhesive according to claim 4, characterized in that: The molar ratio of terephthalic acid, 1,4-cyclohexanedicarboxylic acid, isomannide and ethylene glycol is (97-98): (2-3): (2-2.5): (97.5-98).

6. The protective base film for optical adhesive according to claim 4, characterized in that: The catalyst is an antimony-based catalyst.

7. The protective base film for optical adhesive according to claim 1 or 2, characterized in that: The thickness ratio of the first surface layer, the core layer and the second surface layer is (4-4.5): (91-92): (4-4.5).

8. A method for preparing a protective base film for optical adhesive, characterized in that: The following steps are involved: S1: Preparation of functional masterbatch; S2: The raw materials of the first surface layer, the core layer and the second surface layer are melted separately and cast into sheets; S3: The molded casting is preheated for the first time, stretched longitudinally, and cooled for the first time; S4: the longitudinally stretched cast sheet is sequentially subjected to a second preheating, heating and transverse stretching, heat setting and a second cooling to obtain the protective base film; The raw material melting of the core layer adopts a single screw, and the temperature of the melt extruder is set to 180±2℃, 270±2℃, 280±2℃, 285±2℃, 285±2℃, 285±2℃, 285±2℃, 285±2℃, 285±2℃, 280±2℃ in sequence, and the temperature of the metering extruder is set to 270-280℃; The raw material melting of the first surface layer and the second surface layer adopts a twin-screw, and the melting and metering are integrated. The extrusion temperatures are set to 290±2℃, 290±2℃, 285±2℃, 280±2℃, 275±2℃, 270±2℃, and 270±2℃ respectively.

9. The method for preparing a protective base film for optical adhesive according to claim 8, characterized in that: During the preparation of the functional masterbatch in S1, the temperature of the raw material mixing and melting is 290-295°C.

10. The method for preparing a protective base film for optical adhesive according to claim 8, characterized in that: In S3, the first preheating temperature is 60-90° C., the longitudinal stretching temperature is 70-100° C., the longitudinal stretching ratio is 3-3.6 times, and the longitudinal stretching rate is 80-120 m / min; In S4, the second preheating temperature is 60-90° C., the transverse stretching temperature is 180-200° C., the transverse stretching ratio is 3-3.8 times, and the transverse stretching rate is 80-120 m / min; The heat setting temperature is 220-240°C.

Citation Information

Patent Citations

  • Preparation method of modified nanometer precipitated barium sulfate

    CN101948636A

  • Optical polyester film and preparation method thereof

    CN114103364A

  • Polyester film for lithium battery diaphragm process protection and preparation method thereof

    CN115447236A

  • High-light-transmittance PET (Polyethylene Terephthalate) anti-fog film and preparation method thereof

    CN117467180A

  • Biaxially oriented polyester film with high temperature resistance, high flatness and high reflectivity and preparation method thereof

    CN118181918A

Cited By

  • Polyester film

    CN121552774A